If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4x + -4(x + -1) = -32 + -4 Reorder the terms: -4x + -4(-1 + x) = -32 + -4 -4x + (-1 * -4 + x * -4) = -32 + -4 -4x + (4 + -4x) = -32 + -4 Reorder the terms: 4 + -4x + -4x = -32 + -4 Combine like terms: -4x + -4x = -8x 4 + -8x = -32 + -4 Combine like terms: -32 + -4 = -36 4 + -8x = -36 Solving 4 + -8x = -36 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -8x = -36 + -4 Combine like terms: 4 + -4 = 0 0 + -8x = -36 + -4 -8x = -36 + -4 Combine like terms: -36 + -4 = -40 -8x = -40 Divide each side by '-8'. x = 5 Simplifying x = 5
| 12+2p=3(4-5p) | | 2b-4-6b-6= | | 2.4h+1=7 | | -10n+3(8+8n)=-6(n+4) | | 75=42-3x | | 2(x-2)+3x=-6-8 | | 16=.432h-10.44 | | 16=.432-10.44 | | -3(5n-4)+3n= | | 2x+10-4x-5= | | -2.2x-3.35=6.25+x | | 4L-3=25 | | 15x-20=-3x+16 | | 4+c= | | 4xc= | | (x+4)(x+3)=18 | | 3x+4x=10 | | 4-3x=3.5 | | 10(x+5)=3(x+33) | | 4-3x=-15 | | 3(x-5)=57-5x | | 1000+600+6x=750+400+9x | | 2x-8=96-11x | | 15-y=13 | | 6-6k-2k= | | 2*(x+3)=8 | | 0=x^2+4x-3 | | 2(3x+4)=3x+2[3(x-1)+2] | | 1*2=2 | | 5*(x+19)= | | 2(3x+4)=3x+2[3x-10+2] | | 22+r=37 |